2012
DOI: 10.1016/j.wem.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Background Rates of Acute Mountain Sickness-Like Symptoms at Low Altitude in Adolescents Using Lake Louise Score

Abstract: This study shows that adolescents at low altitude reported a background incidence of symptoms that at high altitude would lead to a diagnosis of AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Among the remaining 102 articles, 7 were excluded from the summary measures including 1 study that was limited to children aged 4 to 11 years at 1605 m (5300 ft) of altitude 43 and a study of teenagers hiking at low altitudes but not associated with mountain sickness. 44 The final selection comprised 91 articles (66 944 participants) for AMS prevalence (eTable 2 in the Supplement) using 6 different instruments: the AMS-C, Hackett clinical score, the LLQS, the Chinese AMS score, the VAS(O), and the CFS.…”
Section: Resultsmentioning
confidence: 99%
“…Among the remaining 102 articles, 7 were excluded from the summary measures including 1 study that was limited to children aged 4 to 11 years at 1605 m (5300 ft) of altitude 43 and a study of teenagers hiking at low altitudes but not associated with mountain sickness. 44 The final selection comprised 91 articles (66 944 participants) for AMS prevalence (eTable 2 in the Supplement) using 6 different instruments: the AMS-C, Hackett clinical score, the LLQS, the Chinese AMS score, the VAS(O), and the CFS.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ]. Studies performed at lower altitudes, reported AMS incidence ranging from 7.3% to 11.3% [ 54 ]. These findings suggest that at similar altitudes, the AMS incidence on children population is heterogeneous and can be associated with intrinsic factors such as gender and BMI [ 35 ] or extrinsic factors that are probably the same as those identified for adults, such as altitude reached, velocity of ascent, previous upper respiratory tract infection (URTI) and time spent at HA.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, due to the unique characteristics of the Antarctic physical environment, the polar conditions may have magnified the risk of AMS when compared to incidence rates at similar altitudes [17,19,30]. Another reason for intensified AMS incidences may be related to false-positive results related to the confounding effects of "altitude-like symptoms" such as travel, change in routine, and anxiety [31]. In addition, the use of acetazolamide did not appear to reduce the incidence of AMS and had no statistical significance on activity data.…”
Section: Discussionmentioning
confidence: 99%